2020
DOI: 10.1097/md.0000000000021462
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in emergency medicine physicians

Abstract: Background: Physician burnout has been a global problem that affects severely the mental status among doctors, especially in emergency medicine (EM). However, few studies have focused on emergency medicine physicians, and the published data are inconsistent. Thus, this meta-analysis is performed to systematically evaluate the prevalence of burnout among emergency medicine physicians. Methods: We systematically searched databases including PubMed, Embase, PsychINFO and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 34 publications
0
28
1
2
Order By: Relevance
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety ( n = 103), depression ( n = 73), stress ( n = 68), fear ( n = 61), burnout ( n = 25), mental distress/health ( n = 21), and post-traumatic stress disorder (PTSD) ( n = 14) (Additional File 3 ). Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixtee...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common psychological symptoms measured with surveys or validated questionnaires reported included anxiety ( n = 103), depression ( n = 73), stress ( n = 68), fear ( n = 61), burnout ( n = 25), mental distress/health ( n = 21), and post-traumatic stress disorder (PTSD) ( n = 14) (Additional File 3 ). Most COVID-19 studies reported on physicians from USA ( n = 23) [ 41 , 52 , 66 , 70 , 77 , 90 – 107 ], China ( n = 22) [ 15 , 49 , 54 56 , 65 , 68 , 73 , 86 , 89 , 102 , 108 118 ] followed by India ( n = 21) [ 40 , 50 , 58 , 63 , 67 , 71 , 102 , 119 – 132 ] [ 41 , 52 , 66 , 70 , 77 ], Italy ( n = 10) [ 32 , 94 , 102 , 125 , 133 138 ], and Turkey ( n = 11) [ 35 , 44 , 94 , 139 – 146 ] [ 28 , 30 , 32 , 34 , 36 , 37 , 42 , 45 , 47 , 48 , 59 , 60 , 62 , 80 , 87 ]. .Sixtee...…”
Section: Resultsmentioning
confidence: 99%
“…Physicians working more days, with higher patient volumes, or with increased duties than before than pandemic also had an increased prevalence of psychological symptoms [ 96 , 101 , 122 , 128 , 149 , 187 , 192 , 195 , 198 ]. Eighteen studies reported on insomnia [ 32 , 35 , 36 , 54 , 65 , 69 , 88 , 114 , 128 , 145 , 149 , 163 , 175 , 177 , 181 , 188 , 192 , 194 ], which is associated with psychiatric disorders and is a risk factor for depression and anxiety [ 15 , 32 , 54 , 65 , 69 , 199 , 200 ]. During the SARS outbreak, physicians of Asian descent felt more stigmatized than their Caucasian colleagues (Canada) [ 15 , 32 , 35 , 36 , 46 , 54 , 65 , 69 , 88 , 114 , 128 , 145 , 149 , 163 , 175 , 177 , 181 , 188 , 192 , 194 , 199 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several systematic reviews explored this issue, reporting the lowest values of burnout prevalence from 6% [34] to 25.4% [36] and the highest from 41% [19] to 71.4% [36]. Moreover, considering the different dimensions of burnout, the prepandemic prevalence of highly burned-out ICU/ED professionals was remarkable, being approximately around 40% for high emotional exhaustion, high depersonalization, and low personal accomplishment [37,38]. Thus, although it seems clear that a great percentage of ICU/ED staff is currently suffering from burnout, this population has presented a high prevalence of this condition for a long time, and there is not sufficient evidence to understand if such prevalence increased due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence observed here is also higher than that in previous Chinese studies [ 19 21 ], but those studies were limited to specific regions or cities. Nevertheless, a recent meta-analysis reveals that 40% emergency medicine physicians have high levels of EE and DP [ 26 ]. The differences might be due to fundamental differences in the medical systems between China and the West.…”
Section: Discussionmentioning
confidence: 99%